In quest of fairness - Zaman, Mohammad Ameeruz (Dhaka : The University Press Limited, 2011)
Articles on Bangladesh's electoral system, governance, and judiciary; previously published in various newspapers.
Keywords: Elections -- Bangladesh; Justice, Administration of -- Political aspects -- Bangladesh; Bangladesh -- Politics and government